Nihilizm jako literackie pogranicze oraz pole napięć aksjologicznych i estetycznych na przykładzie twórczości Jarosława Marka Rymkiewicza. Próba rozpoznania - Kalandyk, Mariusz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
The subject is an attempt to describe the evolution of the term „nihilism” in philosophy (hermeneutics) at the turn of centuries and the description of how this evolution influenced the ways of analyzing literary phenomena. The author wants to present judgements which revalue the approach to this way of thinking deeply rooted in culture. Nihilism in presented approaches appears to be a world view and esthetic phenomenon opening new field of interpretation of poetic and prose texts. The exemplary literary material displaying the possibilities of different interpretations of an artistic text, both an essay and a poem is the output of Jarosław Marek Rymkiewicz.
Nihilism as literary borderland and the area of axiological and esthetic tensions on the example of Jarosław Marek Rymkiewicz’s works. An attempt to recognition
Keywords: nihilism; hermeneutics; existence; Being; cerebration; Speculative Realism; nature; language; pure arbitrarity; nihilizm; hermeneutyka; byt; Bycie; cerebracja; Spekulatywny Realizm; natura; język; czysta arbitralność